Feasibility of Muscle Synergy Outcomes in Clinics, Robotics, and Sports: A Systematic Review - Juri Taborri; Valentina Agostini; Panagiotis K. Artemiadis; Marco Ghislieri; Daniel A. Jacobs; Jinsook Roh; Stefano Rossi (Applied Bionics and Biomechanics)
In the last years, several studies have been focused on understanding how the central nervous system controls muscles to perform a specific motor task. Although it still remains an open question, muscle synergies have come to be an appealing theory to explain the modular organization of the central nervous system. Even though the neural encoding of muscle synergies remains controversial, a large number of papers demonstrated that muscle synergies are robust across different tested conditions, which are within a day, between days, within a single subject, and between subjects that have similar demographic characteristics. Thus, muscle synergy theory has been largely used in several research fields, such as clinics, robotics, and sports. The present systematical review aims at providing an overview on the applications of muscle synergy theory in clinics, robotics, and sports; in particular, the review is focused on the papers that provide tangible information for (i) diagnosis or pathology assessment in clinics, (ii) robot-control design in robotics, and (iii) athletes’ performance assessment or training guidelines in sports.